The double dividend in the presence of abatement technologies and local external effects - Geir H. Bjertnæs; Marina Tsygankova; Thomas Martinsen (Statistics Norway, Research Department, 2012)
This study tests whether the strong double dividend hypothesis holds within a setting where a uniform tax on green house gas emissions is raised above the international quota price within the Norwegian economy. The hypothesis does not hold within a framework where detailed technology choices contribute to lower the revenue recycled back to households. The hypothesis, however, holds when local external effects connected to cuing and accidents etc. within the transport sector are taken into consideration. The hypothesis also holds when the international quota price is increased, and oil prices drop in the long run
Keywords: F41; H21; Q43; Q48; 330; Doublel dividend; emissions